Clumped isotope bottom water temperature record data from Ocean Drilling Program (ODP) Site 747 (IEDA: EarthChem Library)
This dataset contains D47, d18O and d13C data measured on middle Miocene benthic foraminifera from Ocean Drilling Program (ODP) Site 747. We provide replicate-level raw data to allow for data reprocessing.